Tema dan Amanat Sastra Nusantara menurut Apresiasi Mahasiswa melalui Teknologi Informasi Digital - Damayanti, Welsi; Harini, Yostiani Noor; Lushinta, Istiqomah Putri (Raja Zulkarnain Education Foundation, 2024)
This research aims to describe: 1) themes of Indonesian literature according to student appreciation through digital information technology; the mandate of Indonesian literature according to student appreciation through digital information technology; 3) harmony between the message and themes of Indonesianliterature according to student appreciation through digital information technology. The population of this study were students of the Indonesian Language and Literature Education Study Program, Indonesian Education University who filled out and submitted the Google form. They numbered 61 students, divided into 30 students who submitted at the first opportunity and 31 students who submitted at the last opportunity. The sample members were set at 61. This means that this research uses the total sample. Data on themes and messages of Indonesian literature according to student appreciation were collected using a questionnaire instrument via the Google Form short answer option application. A checklist is used to validate each item of the instrument and the results of the analysis of themes and main messages of Indonesian literature. Data were analyzed using descriptive statistical procedures, namely the mode for problem formulation-1 and problem formulation-2. For problem formulation-3, qualitative analysis was used through a thematic approach. Research results: 1) themes of Indonesian literature according to student appreciation through digital information technology, modes of love, fortitude, lies and loss; 2) the message of Indonesian literature according to student appreciation through digital information technology is related to calls and suggestions about love, fortitude, lies and loss; 3) There is no harmony between the message and theme of Indonesian literature according to students' appreciation through digital informationtechnology.